Accuracy modeling and analysis for a lock-or-release mechanism of the Chinese Space Station Microgravity Platform. (December 2018) - Ding, Jian; Liu, Jinguo; Zhang, Rongpeng; Zhang, Lu; Hao, Guangbo
Highlights: We present two accuracy models for the L/R mechanism to analyze the mechanism output errors. We investigate the lead screw errors of the mechanism from the transmission train with DOE. Two accuracy models for the L/R mechanism are verified through DOE with MC simulation, with their relations applied in accuracy analysis. The statistical model for non-synchronous error of the mechanism reveals the orientation errors prevail other errors. Abstract: With development of Chinese space science and technology, plenty of microgravity experiments will be conducted in the Chinese Space Station to be built, and therefore demand for high-precision electromechanical equipment increases substantially. In this paper, a comprehensive accuracy analysis of a new type of auto lock-or-release (L/R) mechanism, which is applied in the Space Station Microgravity Platform (SSMP), is implemented. Firstly, two models (vector analysis model and vector differential model) are, therefore, proposed to analyze output errors of the mechanism. Due to transmission errors from the transmission chain of the gear mechanism, influence factors on axial errors of lead screws are analyzed using design of experiment (DOE) for factor sensitivities. It shows that manufacturing tolerances of the lead screw is the dominant factor. Then, verification of the two proposed accuracy models is comparatively implemented through Monte Carlo (MC) simulation and DOE. Using the present accuracy model, location errors of the lead screw throughout the mechanism's working stroke are illustrated, where the non-synchronous error of the mechanism is particularly discussed. A linear relation between the variance of the non-synchronous error and that of the structural error is established, followed by analyzing influence factors on the non-synchronous error.